Habitual chocolate intake and type 2 diabetes mellitus in the Maine-Syracuse Longitudinal Study: (1975–2010): Prospective observations. (1st January 2017) - Crichton, Georgina E.; Elias, Merrill F.; Dearborn, Peter; Robbins, Michael
Abstract: Compounds in cocoa and chocolate have established cardiovascular benefits, including beneficial effects on insulin resistance, a risk factor for type 2 diabetes mellitus. The aims of this study was to investigate relations between habitual chocolate intakes and diabetes mellitus. Cross-sectional and prospective analyses were undertaken on 953 community-dwelling participants (mean age 62 years, 59% women) from the Maine-Syracuse Longitudinal Study (MSLS). Habitual chocolate intakes, measured using a food frequency questionnaire, were related to prevalence of diabetes mellitus (cross-sectionally) and with risk of diabetes measured approximately five years later (prospectively). We also examined the relation between diabetes (the predictor) and chocolate consumption (the outcome) up to 30 years later. Chocolate intake was inversely associated with type 2 diabetes. Compared to participants who consumed chocolate more than once per week, those who never or rarely ate chocolate exhibited a significantly higher odds of having type 2 diabetes 5 years later (OR: 1.91, 95% CI: 1.03, 3.55, p = 0.04), after adjustment for cardiovascular, lifestyle and dietary factors including other polyphenol-rich beverages. However, individuals diagnosed with diabetes prior to the nutritional assessment consumed lower amounts of chocolate at the time of the dietary assessment. Our findings suggest that relations between chocolate and type 2 diabetes may be bi-directional.